Influence of the first wave of COVID-19 on Chinese students’ psychology and behavior: a case study approach - Zhang, Xiudi; Bian, Liang (Frontiers in Psychiatry, 2024)
During the first wave of COVID-19, China demonstrated a strong commitment to epidemic prevention and control. To safeguard the well-being of teachers and students, universities implemented various measures. This study focuses on Z University, which adopted closed management, and examines its impact on students' psychology and behavior through interviews with 10 students. The research reveals that while students perceive closed management as enhancing safety and promoting learning engagement to some extent, it also has adverse effects on their physical health, psychology, and social life. These impacts included deteriorating physical health, feelings of rebellion and depression regarding college life, alongside concerns and aspirations regarding future job stability. These findings shed light on the support needs of students and offer insights for future development. Higher education institutions can utilize this information to shape policies and procedures, particularly concerning mental health and risk communication, not only during the current pandemic but also in future emergency or disaster scenarios.